Superparamagnetic Poly (3-Hydroxybutyrate-Co-3 Hydroxyvalerate) (Phbv) Nanoparticles for Biomedical Applications - Altbir-Drullinsky, D; Gutierrez-Cutino, M; Gutierrez-Cutino, M; Escobar-Donoso, R; Casagrande-Denardin, J (2013)
Background: The progress in material science and the recent advances in biodegradable/biocompatible polymers and magnetic iron oxide nanoparticles have led to develop innovative diagnostic and therapeutic strategies for diseases based on multifunctional nanoparticles, which include contrast medium for magnetic resonance imaging, agent for hyperthermia and nanocarriers for targeted drug delivery. The aim of this work is to synthesize and characterize superparamagnetic iron oxide (magnetite), and to encapsulate them into poly (3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) nanoparticles for biomedical applications. Results: The magnetite nanoparticles were confirmed by X-ray diffraction and exhibited a size of 22.3 ± 8.8 nm measured by transmission electron microscopy (TEM). Polymeric PHBV nanoparticles loaded with magnetite (MgNPs) were analyzed using dynamic light scattering and showed a size of 258.6 ± 35.7 nm and a negative zeta potential (-10.8 ± 3.5 mV). The TEM examination of MgNPs exhibited a spherical core-shell structure and the magnetic measurements showed in both, non-encapsulated magnetite and MgNPs, a superparamagnetic performance. Finally, the in vitro studies about the magnetic retention of MgNPs in a segment of small intestine of rats showed an active accumulation in the region of the magnetic field. Conclusions: The results obtained make the MgNPs suitable as potential magnetic resonance imaging contrast agents, also promoting hyperthermia and even as potential nanocarriers for sitespecific transport and delivery of drugs. © 2013 by Pontificia Universidad Católica de Valparaíso, Chile.